Pengaruh Earning Pershare, Current Ratio dan Debt To Assets Ratio Terhadap Return On Asset Pada Indeks Saham Syariah Indonesia: Studi Pada Perusahaan Sektor Pertambangan Periode 2016 -2022 - Olyvia Rosalia; Rafidah Rafidah; Solichah Solichah (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted on Mining sub-sector companies listed on the Indonesian Sharia Stock Index. The purpose of this research is to know, analyze, and explain the influence between the variables of Market Ratio (Earning Per Share), Liquidity Ratio (Current Ratio) and Solvency Ratio (Debt to Assets Ratio) on Profitability Ratio (Return On Assets). The method in this study is a quantitative method. Data collection in this study was carried out using secondary data in the form of annual reports and published financial reports. Annual report data and panel data financial reports for 2016-2022. In this study, the amount of panel data is 77 data, which consists of 11 mining companies with a span of 7 years. The results of this study partially show that the market ratio variable (Earning Per Share) has a positive and significant effect on the profitability ratio (Return On Assets), the liquidity ratio variable (Current Ratio) has a significant effect on the profitability ratio (Return On Assets), the solvency ratio variable (Debt to Assets Ratio) has no effect on the profitability ratio (Return On Assets). Simultaneously shows that the market ratio variable (Earning Per Share), liquidity ratio (Current Ratio), and solvency ratio (Debt to Assets Ratio) together have a significant effect on the profitability ratio variable (Return On Assets). Based on the results of this study, companies must be able to maintain and increase profits and optimally utilize their resources.